The Influence of The Inflation Rate and The Interest Rate of Bank Indonesia Certificates on The Composite Stock Price Index With The Us Dollar Exchange Rate As A Moderating Variable on The Indonesia Stock Exchange - Septiani, Dwi (Universitas Pamulang, 2020)
This study aims to determine how the influence of the inflation rate and the interest rate of Bank Indonesia Certificates (SBI) on the Composite Stock Price Index (IHSG) with the US dollar exchange rate as a moderating variable on the Indonesia Stock Exchange 2007-2016. The data of this research consists of inflation rate reports, Bank Indonesia Certificate interest rate reports, US dollar exchange rate reports and reports on the Composite Stock Price Index for 120 (one hundred and twenty) months, starting from 2007 to 2016. Methods The research used in this research is associative research with quantitative data analysis. Data calculation was performed by using multiple regression analysis of the relationship, t test, F test and the coefficient of determination R2. Meanwhile, to test the moderating variable using the interaction test. The inflation rate variable (X1) and the interest rate for Bank Indonesia Certificates (SBI) (X2) with the US dollar exchange rate (X3) as the moderating variable simultaneously have a positive and insignificant effect on the Composite Stock Price Index (IHSG) (Y) on the Stock Exchange. Indonesia 2007-2016. The coefficient of determination of 0.596065 means it is known that the influence of the inflation rate variable (X1) and the interest rate for Bank Indonesia Certificate (SBI) (X2) with the US dollar exchange rate (Z) as the moderating variable is 59.61% while the rest 40.39% is explained by other variables that are not explained and examined in this study. Keywords: Inflation Rate, Bank Indonesia Certificate Interest Rate, US Dollar Exchange Rate and Composite Stock Price Index